The Influence Of Regional Dialects And Accents On The English Phonological Competence Of EFL Students - Yani Lubis; Aulia Rahma; Dillo Sarwana; Fika Mardiani; Putri Afsila Balqis Barus (JOURNAL SAINS STUDENT RESEARCH, 2026)
The purpose of this study is to see how regional dialects and accents affect the phonological ability of EFL (English as a Foreign Language) students in Indonesia. The background of this research lies in the sociolinguistic situation in Indonesia where students usually master the regional language as their first language before starting to learn English. Phonological interference, which impacts students' pronunciation abilities, can be caused by differences in phonological systems between the first language and English. The focus of this study was to find the types of phonological aberrations in students' English pronunciation. Data were obtained through observation of pronunciation, documentation of speech results, and analysis of the form of sound realization of EFL students. Data analysis was carried out by data reduction methods, phonological error classification, interpretation, and conclusion drawn. The results showed that regional accents and dialects had a significant effect on students' phonological abilities. Sound substitution (sound substitution), phonological simplification (phonological simplification), epenthesis (addition of sounds), final consonant removal (final consonant removal), and orthographic impact on pronunciation are some of the major forms of phonological error. The primary cause of these errors is first language (L1) interference, specifically the structural and phonotactic differences between the students' native regional languages and the English phonological system. According to this study, the goal of learning pronunciation is not to eliminate accents, but to improve a person's comprehension so that they can communicate well in English.